Modification-free carbon dots as turn-on fluorescence probe for detection of organophosphorus pesticides. (15th April 2018) - Lin, Bixia; Yan, Yun; Guo, Manli; Cao, Yujuan; Yu, Ying; Zhang, Tingyun; Huang, Yan; Wu, Duo
Highlights: Turn-on probe based on modification-free C-dots was constructed. A universal and simple detection method for OPs was established. Imaging of OPs could be used for on-site visual assay of OPs in vegetable samples. Abstract: It is important to detect pesticides residues due to the concern over food safety. In this work, the burning ash of waste paper was used as carbon source to synthesize carbon dots (C-dots). The fluorescence of obtained C-dots could been turn off by Fe 3+ which was from Fe 2+ oxidized by H2 O2, organophosphorus pesticides could effectively inhibit the production of H2 O2 by destroying the acetylcholinesterase activity, so the fluorescence of C-dots hold turning on in the presence of organophosphorus pesticides. Based on above principle that the fluorescence intensity of C-dots was proportional to the pesticides concentration, take chlorpyrifos for example, a universal method for pesticides detection was established. The linear range was 0.01–1.0 μg/mL with detection limit of 3 ng/mL. The method was reliable and sensitive to actual samples. The imaging of chlorpyrifos on cabbages leaves indicated this method could be used for visualization detection of organophosphorus pesticides in vegetables.